The radio narratives of Walter Benjamin: teaching of cultural history and political formation - da Silva, Andréa Giordanna Araujo (Revista Crítica Histórica, 2017)
The article presents a preliminary reflection of the pedagogical contents manifested in the narratives that compose the work “Children's Hour: Walter Benjamin's radio narratives”. The production brings together a set of 30 radio lectures produced between the years 1927 and 1932, when the author presented, in two German radios, educational-cultural transmissions intended for children. The compilation was divided, for analysis, into three thematic groups: social and environmental accidents, history and culture of marginalized subjects and other topics. The study made it possible to identify the approach of the concept of experience, developed in the texts “Experience” (1913) and “Experience and Poverty” (1933), of the themes selected for pedagogical-radio work with children in the context of foundation of the totalitarian government.